2020
DOI: 10.3390/nu12051235
|View full text |Cite
|
Sign up to set email alerts
|

Potato Protein Isolate Stimulates Muscle Protein Synthesis at Rest and with Resistance Exercise in Young Women

Abstract: Skeletal muscle myofibrillar protein synthesis (MPS) increases in response to protein feeding and to resistance exercise (RE), where each stimuli acts synergistically when combined. The efficacy of plant proteins such as potato protein (PP) isolate to stimulate MPS is unknown. We aimed to determine the effects of PP ingestion on daily MPS with and without RE in healthy women. In a single blind, parallel-group design, 24 young women (21 ± 3 years, n = 12/group) consumed a weight-maintaining baseline diet contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…Insofar as plant protein isolates are concerned, leucine content is similar to some animal-based sources (>90%) [ 109 ]. For example, potato protein isolate has the highest leucine content of most commercially available plant-based protein isolates, similar to animal-derived proteins [ 109 , 110 ]. However, there is a lack of studies that have examined the efficacy of plant-based protein isolates compared with animal-derived protein sources to stimulate MPS and, by extension, increase skeletal muscle mass and strength in older adults.…”
Section: The Importance Of Protein Intakementioning
confidence: 99%
“…Insofar as plant protein isolates are concerned, leucine content is similar to some animal-based sources (>90%) [ 109 ]. For example, potato protein isolate has the highest leucine content of most commercially available plant-based protein isolates, similar to animal-derived proteins [ 109 , 110 ]. However, there is a lack of studies that have examined the efficacy of plant-based protein isolates compared with animal-derived protein sources to stimulate MPS and, by extension, increase skeletal muscle mass and strength in older adults.…”
Section: The Importance Of Protein Intakementioning
confidence: 99%
“…Interestingly, some types of plant-derived proteins (e.g., potato and quinoa) contain adequate amounts of all EAA [9] and thus may offer sufficient anabolic alternatives to animal-derived proteins. Indeed, a recent study in young women found that 25 g of potato protein twice daily for 2 weeks (1.6 g/kg/d total protein) increased integrated MPS above baseline at rest, with no increase observed in those consuming a control diet (0.8 g/kg/d total protein) [102]. Whilst this greater anabolic response could be attributed simply to the greater amount of protein, it still demonstrates the ability of potato protein to stimulate MPS above a baseline diet already containing the RDA of protein, at least in younger individuals.…”
Section: Skeletal Musclementioning
confidence: 99%
“…This may be due to the slower nature of casein digestion and subsequent aminoacidemia, with whey protein increasing aminoacidemia to a more rapid and greater degree than intermediary soy protein [ 97 ]. Conversely, comparable MPS stimulation was observed post-exercise in those consuming potato protein (25 g twice daily) and control diet groups over a 2-week period, highlighting the potency of RE as an anabolic stimulus [ 102 ]. In the context of ageing, a randomised cross-over study by Wilkinson et al [ 103 ] found that the ingestion of soy protein (18.2 g) with acute RE increased MPS responses to a lesser degree than that of isonitrogenous whey protein in young males.…”
Section: Plant-derived Proteins: Effects In Relation To Age Exercmentioning
confidence: 99%
“…The consumption of plant-based protein sources such as blends of different proteins (50) , or plant-based protein isolates (i.e. wheat, potato or pea protein) (46,52) have proven to be potential alternatives to animal-based protein in young adults. To date, however, the consumption of such protein blends and their effects on muscle anabolism in older adults are unclear.…”
Section: Plant-based and Animal-based Proteinsmentioning
confidence: 99%